THE ROLE OF REGIONAL HEAD CANDIDATE SURVEYS IN POLITICAL PARTY DECISION-MAKING: A STATE ADMINISTRATIVE LAW ANALYSIS - Arifin, Firdaus (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
The use of candidate surveys in the determination of candidates for regional heads by political parties is an increasingly common practice, but its effects on the legitimacy of political decisions and state administration have not been widely studied. This research aims to explore the role of candidate surveys as an instrument of legitimacy in the context of state administrative law and identify its impact on fairness and transparency. The research method used is qualitative analysis through interpretation of primary legal materials by referring to legal doctrines and relevant theories. The results showed that from the perspective of state administrative law, surveys of candidates for regional heads can strengthen the legitimacy of political decisions by providing evidence of public support, but also potentially pose a risk of manipulation and methodological bias that can undermine fairness in the state administrative system. The implications of these findings highlight the need to improve survey methodologies, implement strict regulations, and conduct effective oversight to ensure transparency and accuracy. This research provides valuable insights into how candidate surveys of regional head candidates can be used fairly and effectively in political processes and public administration.